Comparing the MSIS-29 and the Health Utilities Index Mark III in Multiple Sclerosis - Marrie, Ruth Ann; Dolovich, Casandra; Cutter, Gary R.; Fox, Robert J.; Salter, Amber (Frontiers in Neurology, 2021)
Objective: Since the properties of health-related quality of life measures vary across samples, studies directly comparing the properties of different measures can be useful in understanding their relative strengths and limitations. We aimed to compare the psychometric properties of the Health Utilities Index Mark III (HUI3) and the Multiple Sclerosis Impact Scale-29 (MSIS-29). Methods: In Spring 2020, North American Research Committee on Multiple Sclerosis (NARCOMS) Registry participants completed the HUI3, MSIS-29, Patient Determined Disease Steps (PDDS) and SymptoMScreen. For the HUI3 and MSIS-29 we assessed floor and ceiling effects, construct validity, and internal consistency reliability. We used relative efficiency to compare the discriminating ability of the two measures with respect to disability. Results: We included 5664 participants in the analysis, with mean (SD) age 63 (10.1) years; 4579 (80.8%) were women. For the HUI3 the mean (SD) score was 0.44 (0.32), for the MSIS-29 physical it was 34.0 (24.2) and for the MSIS-29 psychological it was 25.9 (20.4). Neither of the measures had floor or ceiling effects, and internal consistency reliability was >0.70 for both. The HUI3 and MSIS-29 physical were strongly correlated (r = -0.78; 95%CI: -0.79, -0.77). The correlation between the HUI3 and MSIS-29 psychological was weaker but remained moderately strong (r = -0.64; 95%CI: -0.66, -0.63). After adjusting for sociodemographic and clinical factors, relative efficiency to discriminate between disability (PDDS) groups was highest for the MSIS-29 physical scale, followed by the HUI3. Conclusion: Both measures had adequate validity and reliability. The MSIS-29 physical discriminated between disability groups better than the HUI3.